APPLICATION OF CUCKOO SEARCH METHOD IN 3D SLOPE STABILITY ANALYSIS FOR LIMESTONE QUARRY MINE - Masagus Ahmad Azizi; Irfan Marwanza; Nadya A. Hartanti; Muhammad K. Ghifari; Afiat Anugrahadi; Zulfahmi Zulfahmi (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2020)
The Cuckoo Search (CS) is a very fast and efficient global optimization method to locating the slip surface which carried out by iteration. However, the Grid Search (conventional method) method in 3D slope stability analysis takes longer than this method on the computation process. Slope stability analysis was performed using the 3D limit equilibrium method “Bishop” with Cuckoo Search of slip surface by maximizing iteration of the simulation and columns in X or Y. To ensure that the slip surface within the global minimum slip surface, the maximum iteration in CS was also specified from 40 to 1200. Based on maximum columns in X or Y, the safety factor value of the 3D CS results was then compared to the Grid Search results to determine the final 3D safety factor and the estimated volume of potential failure. The final 3D safety factor obtained from the average 3D safety factor (with maximum iteration 400, 800, 1000, and 1200) is about 2,01 with the average estimated volume of slope failure of 190.000 m3 that located at the north of the pit.